2008
DOI: 10.1002/bmc.1115
|View full text |Cite
|
Sign up to set email alerts
|

Development of an immunochromatographic assay for rapid detection of 1‐Aminohydantoin in urine specimens

Abstract: A rapid immunochromatographic assay was developed and validated for detection of 1-aminohydantoin (AHD) in urine specimens. Colloidal gold-labeled polyclonal antibody specific to AHD derivative was used as the marker; based on the competitive reactivity theory, the metabolite of nitrofurantoin after derivatization with benzaldehyde would compete with carboxyphenyl AHD derivative-conjugated ovalbumin. The test strip could efficaciously detect the novel analyte with a visual detection limit of 10 ng mL(-1) and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
0
13
1
Order By: Relevance
“…Some immunoassays that detect AOZ residue (Cheng et al, 2009;Cooper, Caddell, Elliott, & Kennedy, 2004;Vass et al, 2005), SEM (Cooper et al, 2007;Gao, Chen, Cheng, Lei, & Zeng, 2007) and AMOZ (Pimpitak et al, 2009) residues have already been reported. In addition, the detection of the nitrofuran parent drugs has also been reported (Li, Liu, & Wang, 2009;Liu et al, 2007;Xu et al, 2009). However, to the best of our knowledge no ELISA method has been reported to detect AHD residue in animal tissues.…”
Section: Introductionmentioning
confidence: 93%
“…Some immunoassays that detect AOZ residue (Cheng et al, 2009;Cooper, Caddell, Elliott, & Kennedy, 2004;Vass et al, 2005), SEM (Cooper et al, 2007;Gao, Chen, Cheng, Lei, & Zeng, 2007) and AMOZ (Pimpitak et al, 2009) residues have already been reported. In addition, the detection of the nitrofuran parent drugs has also been reported (Li, Liu, & Wang, 2009;Liu et al, 2007;Xu et al, 2009). However, to the best of our knowledge no ELISA method has been reported to detect AHD residue in animal tissues.…”
Section: Introductionmentioning
confidence: 93%
“…Compared to other methods, ICA offers many advantages such as no requirement for instruments, simple operation, cheap price of detection and easy result evaluation. To date, for nitrofurans, there have been only three ICAs published for the detection of 1‐aminohydantoin (AHD, the metabolite of nitrofurantoin) and semicarbazide (SEM, the metabolite of nitrofurazone) . Nevertheless, in these three ICAs, the analyte is the derivative of AHD or SEM rather than the metabolite itself, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the low cost, the use of nitrofurans has been resumed in recent years, which has raised concerns on safety of meat products. For example, in the European market, nitrofuran residues have been detected constantly in poultry and aquaculture products that were exported from Southeast Asia and Latin America (Xu and others 2009). …”
Section: Introductionmentioning
confidence: 99%